2018
DOI: 10.1007/s00359-018-1274-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of spatial texture in visual control of bumblebee learning flights

Abstract: When leaving the nest for the first time, bees and wasps perform elaborate learning flights, during which the location of the nest is memorised. These flights are characterised by a succession of arcs or loops of increasing radius centred around the nest, with an incremental increase in ground speed, which requires precise control of the flight manoeuvres by the insect. Here, we investigated the role of optic flow cues in the control of learning flights by manipulating spatial texture in the ventral and panora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Previous work in different insects has shown that the texture presented in the ventral and lateral field of view is important for flight control (Linander et al 2017 , 2018 ; Portelli et al 2011 ; Straw et al 2010 ). Our results suggest that it would be interesting to do similar experiments in Episyrphys hoverflies, by e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in different insects has shown that the texture presented in the ventral and lateral field of view is important for flight control (Linander et al 2017 , 2018 ; Portelli et al 2011 ; Straw et al 2010 ). Our results suggest that it would be interesting to do similar experiments in Episyrphys hoverflies, by e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We took photos of the ground over which the hoverfly was performing its behavior and panoramic photographs of the surrounding. We focused on images from the ventral and lateral parts of the visual field as these appear to be particularly important for insect flight control (Linander et al 2017 ; 2018 ; Portelli et al 2011 ; Straw et al 2010 ). In addition, panoramic images have been used extensively to understand motion vision coding in the insect brain (for hoverfly examples, see e.g., O’Carroll et al 2011 , 2012 ; Barnett et al 2010 ; Straw et al 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…We discarded the few flights in which bees landed during the learning flight or flew directly away from the nest. Bumblebee learning flights have two phases: an initial phase in which bees fly close to the nest and are low on the ground and a second phase in which they gain height and fly further from the nest (Collett et al, 2013; Linander et al, 2018; Lobecke et al, 2018; Philippides et al, 2013; Riabinina et al, 2014). We stopped analysis of the flights once the bees had travelled 5cm from the nest.…”
Section: Methodsmentioning
confidence: 99%
“…The learning flight of B. terrestris starts with a period of several seconds in which the bee remains within about 5 or 6 cm of the nest hole and a few centimetres above it. The bee then gradually increases its distance from and its height above the nest ( Linander et al, 2018 ). Bumblebees, in this later phase of the flight, perform a sequence of alternating clockwise and anti-clockwise loops, which carry the bees away from and towards the nest ( Philippides et al, 2013 ).…”
Section: Matching Learning and Return Flightsmentioning
confidence: 99%